Implementing of Al Bidayah Method to Improve The Kitab Kuning Reading Skills - Neneng Hasanah; Yuyun Rohmatul Uyuni; Lismawati Lismawati; Fauziah Fauziah; Dirjo Dirjo (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article aims to analyze the application of the al-bidayah method in reading the Kitab Kuning and its obstacles in Islamic boarding schools. The research method uses qualitative methods with an exploratory approach. The research was conducted at the Daar el Hasanah Islamic Boarding School, Jawilan District, Serang Regency, Banten Province. Collecting data through direct observation, interviews with ustadz and students, and document studies. The data processing technique was carried out by means of data verification, data presentation, data reduction, and drawing conclusions from the research results. The data analysis technique of the research results is done by interpreting and concluding the findings. The results showed that the application of the al-bidayah method combined with existing programs at the Daar El Hasanah Islamic Boarding School was very effective in developing the ability of students to read and understand the Kitab Kuning. The obstacles found in the application of the al-bidayah method in reading the Kitab Kuning in the Daar el Hasanah Islamic boarding school are the ability of students to be beginners, to memorize a lot of rules, and to have a solid student learning time. However, this study recommends that the al-bidayah method be applied in teaching how to read the Kitab Kuning in Islamic boarding schools.